Persiapan dan Kendala Implementasi Pendidikan Inklusi di SD Negeri Cisalak 1: Analisis Tantangan dan Solusi - Hening Windria; Asep Supena; Edwita Edwita; Dorotul Yatimah (Journal on Education, 2025)
Inclusive education provides equal learning opportunities for all students, including children with special needs (ABK), in the same school environment. This study analyzes the preparation and challenges faced by SD Negeri Cisalak 1, Depok, as a model inclusive school, using a descriptive qualitative method with data collected through interviews with the principal. The results indicate that SD Negeri Cisalak 1 has taken strategic steps, such as conducting initial assessments to understand the needs of ABK, involving Special Education Support Teachers (GPK), providing facilities like the Learning Support Center (LSC), and implementing parenting programs to engage parents. However, challenges such as limited facilities, uneven teacher competence, social stigma, and resistance from some parents remain obstacles. These issues highlight the need for stronger collaboration between schools, parents, and the government to optimize the implementation of inclusive education.